2010
DOI: 10.1155/2010/705919
|View full text |Cite
|
Sign up to set email alerts
|

Large Intra-Articular Anterior Cruciate Ligament Ganglion Cyst, Presenting with Inability to Flex the Knee

Abstract: A 41-year-old female presented with a 3-month history of gradually worsening anterior knee pain, swelling and inability to flex the knee. Magnetic resonance imaging (MRI) revealed a large intra-articular cystic swelling anterior to the anterior cruciate ligament (ACL), extending into the Hoffa's infrapatellar fat pad. Following manipulation under anaesthesia and arthroscopic debridement of the cyst, the patient's symptoms were relieved with restoration of normal knee motion. ACL ganglion cysts are uncommon int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
0
10
0
Order By: Relevance
“…A ganglion cyst is a synovium-lined structure and is common around the wrist joint, but it is rare in the knee joint. A ganglion cyst in the knee joint often arises from ACL or PCL [ 5 ], but rarely arises from the infrapatellar fat pad. Sugiura et al reported the ganglion cyst arising from the infrapatellar fat pad of 10-year-old boy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A ganglion cyst is a synovium-lined structure and is common around the wrist joint, but it is rare in the knee joint. A ganglion cyst in the knee joint often arises from ACL or PCL [ 5 ], but rarely arises from the infrapatellar fat pad. Sugiura et al reported the ganglion cyst arising from the infrapatellar fat pad of 10-year-old boy [ 6 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported the case of 41-year-old female who presented with a gradually worsening anterior knee pain, swelling and inability to flex the knee. MRI revealed a large intra-articular cystic swelling anterior to ACL, extending into the infrapatellar fat pad [ 5 ]. In a study by Krudwig et al [ 7 ], 76 cases of ganglion cysts were found in 8000 knee arthroscopic examinations.…”
Section: Discussionmentioning
confidence: 99%
“…Mechanical locking, clicking sensation, and stiffness also occur frequently. A ganglion cyst that is located anteriorly at the tibial attachment results in extension block while those located posteriorly produce flexion block [ 19 - 20 ]. Usually, there is no history of knee instability.…”
Section: Reviewmentioning
confidence: 99%
“…In our practice, in addition to the easily accessible wrist ganglia, we commonly use USG guidance for the aspiration/fenestration and injection of ganglions associated with the cruciate ligaments[ 111 112 ] and meniscal cysts[ 113 ] with good symptomatic relief. Persistent pain from iliotibial band friction syndrome also responds to local injection therapy.…”
Section: Interventions In Bursae and Gangliamentioning
confidence: 99%